1987
DOI: 10.1152/ajpendo.1987.253.5.e489
|View full text |Cite
|
Sign up to set email alerts
|

Improved insulin action in muscle, liver, and adipose tissue in physically trained human subjects

Abstract: The present studies were initiated to assess the effect of insulin on muscle, liver, and adipose tissue in eight control and eight physically trained individuals matched for age and body mass index. Results indicated that percent body fat was 53% lower and maximal oxygen consumption 50% higher in physically trained subjects. Although the plasma glucose response to a standard oral glucose challenge was similar in the two groups, the insulin response was significantly lower in the trained individuals (P less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
1
3

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 26 publications
6
54
1
3
Order By: Relevance
“…Although ingested carbohydrate content was larger than in the previous studies, fat metabolism during exercise showed no difference among conditions, which may be influenced by the high capacity for insulin sensitivity in the subjects. Energy metabolism during exercise in athletes and diabetic patients cannot be easily compared because insulin sensitivity is higher in athletes compared with sedentary subjects and such patients, which may have led to the difference between the present study and a previous study (29). CHO absorbed from the intestines into blood after a meal is rapidly taken into muscle cells in athletes, which may have resulted in the phenomenon energy metabolism during exercise did not differ regardless of elapsed time after meal, because compared to the level shown immediately before exercise in the no-meal trial, the serum insulin level was elevated over a shorter interval in the meal trials after the exercise.…”
Section: Discussioncontrasting
confidence: 68%
“…Although ingested carbohydrate content was larger than in the previous studies, fat metabolism during exercise showed no difference among conditions, which may be influenced by the high capacity for insulin sensitivity in the subjects. Energy metabolism during exercise in athletes and diabetic patients cannot be easily compared because insulin sensitivity is higher in athletes compared with sedentary subjects and such patients, which may have led to the difference between the present study and a previous study (29). CHO absorbed from the intestines into blood after a meal is rapidly taken into muscle cells in athletes, which may have resulted in the phenomenon energy metabolism during exercise did not differ regardless of elapsed time after meal, because compared to the level shown immediately before exercise in the no-meal trial, the serum insulin level was elevated over a shorter interval in the meal trials after the exercise.…”
Section: Discussioncontrasting
confidence: 68%
“…34 Moreover, it is well known that endurance training improves insulin sensitivity in young adults as well as in elderly people 35,36 and improved insulin action has been associated with a higher glucose uptake at the muscle level. 35 Moreover, under hyperinsulinaemic hyperglycaemic conditions, insulin andaor glucose have been shown to inhibit fat oxidation by controlling the rate of long chain FFA entrance into the mitochondria. 37 This could be associated with the stimulant effect of insulin and glucose on the production of malonyl-CoA, a powerful inhibitor of the FFA carrier into the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of an arm ergometer training programme, as part of a comprehensive primary rehabilitation programme in recently injured tetraplegic patients, has not previously been studied. Since there is a positive correlation between peak oxygen uptake and whole body glucose uptake in healthy individuals, 17,18 we speculated that endurance training in tetraplegic subjects would similarly lead to increased peak oxygen uptake, and improve whole body glucose disposal.…”
Section: Introductionmentioning
confidence: 99%